Pengaruh Diameter Lubang Udara Terhadap Dinamika Gelembung Udara Dalam Kolom Air - Roy Sardian; Gatut Rubiono; Anas Mukhtar (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2021)
One important process in improving water quality is the aeration process. In carrying out this aeration process it is necessary to use a device called an aerator. The working principle of this tool is to add dissolved oxygen in the water. This research was conducted using an aerator column with a height of 50 cm, a length of 25 cm and a width of 5 cm with freshwater and sea water media. the addition of variations in the form of air hole diameter (needle) with a variation of 1 mm, 1.5 mm and 2 mm and air discharge of 1, 2 and 3 liters / minute. The results showed that the larger the needle diameter, the larger the diameter of the air bubbles in fresh water and sea air. The difference in media between freshwater and sea air affects the diameter of the air bubbles. Keywords - aeration, aerator column, air bubbles